IMPLIKASI TINDAKAN PERATAAN LABA TERHADAP PENGAMBILAN KEPUTUSAN BAGI INVESTOR - Ari Dewi Cahyati (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2010)
Net revenue or earnings often use to evaluate management performance. Therefore management tend to do disfunctional behaviour. One kind of disfunctional behaviour is income smoothing. The purpose of income smoothing is to increase stock price. Income smooting is logic and rationale for manajer with use inherent weakness in incounting. Although income smoothing can reduce reliability of financial statement and disserve of investor because it’s can make investor wrong in decision making, income smoothing is legally practise because not violate generally accepted accounting principles.